Pemetaan Daerah Potensi Longsor di Kecamatan Leihitu Barat, Kabupaten Maluku Tengah, Menggunakan Metode Slope Morphology (SMORPH) - Philia Christi Latue; Daniel Anthoni Sihasale; Heinrich Rakuasa (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
Landslide prone area mapping is an important step in mitigation and natural disaster management efforts in West Leihitu Sub-district, Central Maluku Regency. This research aims to map landslide prone areas in West Leihitu District, Central Maluku Regency, using Slope Morphology (SMORPH) method. This research uses DEMNAS data. The Slope Morphology (SMORPH) method was used in this research to overlay the slope map and slope shape to produce a map of landslide prone areas in West Leihitu Sub-district. The results showed that very low landslide potential class has an area of 465.40 ha (4.47%), low landslide potential class has an area of 4,232.96 ha or 40.63%, medium landslide potential class has an area of 2,524.30 ha or 24.23% and high landslide potential class has an area of 3196.19 ha or 30.68%. The results of this research are expected to be useful for the government and community in West Leihitu Sub-district, Central Maluku Regency in mitigating landslides in the future.